Voltammetric determination of lead in gunshot residue samples - Hussin, Siti Zanariah (Universiti Sains Malaysia, 2016)
Gunshot residue (GSR) produced from the ignition and combustion of mixture of combustible materials in an ammunition mainly consists of three major elements namely lead (Pb), antimony (Sb) and barium (Ba). It can be analyzed using various techniques such as Gas Chromatography Mass Spectrometry (GC-MS), and in this work anodic stripping voltammetric technique was successfully used to detect the concentration of Pb in the sample by application of an electrical potential. The voltammetric parameters used to analyse the sample include stirrer speed at 2000 rpm, equilibrium time at 5 min, pulse amplitude at 50 mV, start potential at -1500 mV, voltage step time at 0.6 s, sweep rate at 10 mV/s, under differential pulse mode. Concentrations of Pb on the cloth targets and cartridge were analysed using voltammetry. The results showed that concentrations of Pb found at the different locations of the targets with a range of 2.677 ±0.106 ppb to 34.09 ± 0.1 14 ppb whereas 66.010 ± 0.229 ppb to 376.700 ± 2.435 ppb in cartridge samples. The concentration of Pb in (GSR) on the cloth target was compared between voltammetric techniques and atomic absorption spectroscopy (AAS) technique, showed that the concentration of Pb obtained using former technique is higher than latter.